Pengaruh Model Pembelajaran Auditory Intellectually Repetition (AIR) Terhadap Pemahaman Konsep Materi Penjumlahan dan Pengurangan Pecahan Kelas V SDN 1 Pangkalpinang - Dini Agustin; Fitri Apriani; Yorenza Meifinda (JBES (Journal Basic Education Skills), 2025)
This research is constrained by the low understanding of the concept of students in mathematics subjects, and the use of conventional learning model that teachers do in the learning process has not been able to improve the understanding of the student concept. This study aims to determine the effect of the study of the Auditory Intellectually Repetition (AIR) learning model on understanding the concept of the materials submission and reduction of the class V SDN 1 Pangkalpinang. This research uses a quantitative method with research design used is true experimental design using the pretest-posttest control group design. The subject study student class V SDN 1 Pangkalpinang amounted to 76 students and consisted of 2 classes. The VA experimental class consist of 38 students, and the VB class control consists of 38 students. Data collection techniques in research using essay tests amounted to 5 questions. Data analysis techniques use the normality test (Kolmogorov Smirnov), the homogeneity test (Levene test), and the hypothesis test using the independent sample t-test. The result of the normality test (Kolmogorov Smirnov) obtained a pretest control class (0.200) and posttest (0.200) for the pretest experimental class (0.147) and posttest (0.171) normal distribution value due to > 0.05. The homogeneity test (Levene) was obtained pretest (0.807) and posttest (0.361); the value of homogeneity was declared because it was > 0.05. The hypothesis test (independent t-test sample) shows that the value of tcount 2.342 > t-table 1.992 significance (0.022 < 0.05), then Ha is accepted, meaning there is an influence of the Auditory Intellectually Repetition (AIR) learning model on understanding the concept of the material addition and subtraction of the class V SDN 1 Pangkalpinang.